Two New Species of Diploderma Hallowell, 1861 (Reptilia: Squamata: Agamidae) from the Hengduan Mountain Region in China and Rediscovery of D. brevicaudum (Manthey, Wolfgang, Hou, Wang, 2012) - Wang, Kai; Gao, Wei; Wu, Jiawei; Dong, Wenjie; Feng, Xiaogang; Shen, Wenjing; Jin, Jieqiong; Shi, Xiudong; Qi, Yin; Siler, Cameron D.; Che, Jing (Zootaxa, 2021)
Recent studies have highlighted the underestimated diversity of the genus Diploderma Hallowell, 1861 in the Hengduan Mountain Region in Southwest China, but much of the region remains poorly surveyed for reptile diversity. In this study we describe two new species of Diploderma from the upper Jinsha and middle Yalong River Valley, based on evaluations of morphological, genetic, and distribution data. The two new species are morphologically most similar to D. angustelinea and D. vela, but they can be diagnosed from both recognized taxa and all remaining congeners by a suite of morphological features, particularly the distinct coloration of gular spots. Additionally, both new species either render other recognized species paraphyletic or are allopatric with respect to their morphologically similar congeners. Furthermore, we rediscover D. brevicaudum in the wild for the first time, which was known from historical museum specimens only. We estimate the phylogenetic position of D. brevicaudum within the genus Diploderma based on mitochondrial genealogy, and we provide an expanded diagnosis and comparisons against closely related congeners and provide a detailed description of coloration in life based on newly collected specimens. Our discoveries of the new Diploderma species further highlight the urgent conservation needs of the currently neglected hot-dry valley ecosystems in the Hengduan Mountain Region of China.